Measuring dynamic return and volatility connectedness among Nigerian financial markets - Elias A. Udeaja (CBN Journal of Applied Statistics, 2019)
This study employs the connectedness measure of Diebold and Yilmaz (2012, 2014) to examine the intensity of connectedness among the Nigerian financial markets for the period January 2000 to December 2018. The study used all shares index, Treasury bill rate and Naira/USD official exchange rate to measure stock market, money market and exchange rate market, respectively. The study found connectedness among the Nigerian financial markets to be highly time-varying and appear to be higher during the period of high depreciation of the naira which coincides with the period of falling oil prices and domestic economic meltdown of 2014 and 2016, respectively. This shows that, relative to external shocks, connectedness among financial markets is likely to get amplified during the time of domestic turbulence. The paper, therefore recommends that policymakers should look inward whenever policy discuss revolves around the increasing integration of financial markets to save the economy from aggravation of contagion.
Keywords: C58; F36; G11; G12; 330; Connectedness; Financial Market; Nigeria; Return; Spillover; Volatility